Analisis Efektivitas Mindfulness Breathing dengan Guided Imagery Dalam Menurunkan Kecemasan Ibu Post Sectio Caesarea Di RSUD I.A Moies Samarinda - Windu Pahrian; Pipit Feriani; Tri Wahyuni; Joanggi Wiriatarina Harianto (Indonesian Journal Publisher, 2026)
Post–Sectio Caesarea (SC) mothers are vulnerable to anxiety due to postoperative pain, limited mobility, and concerns regarding their maternal role and recovery process. If left unmanaged, anxiety can negatively affect maternal well-being, breastfeeding, and mother–infant bonding. Nonpharmacological interventions such as Mindfulness Breathing and Guided Imagery are considered safe and effective in reducing anxiety. This study aimed to analyze the effectiveness of a combination of Mindfulness Breathing and Guided Imagery in reducing anxiety levels among post–Sectio Caesarea mothers at RSUD I.A. Moeis Samarinda. The study employed a managed case study approach using the nursing care process, which included assessment, diagnosis, intervention, implementation, and evaluation. The subjects were post–Sectio Caesarea mothers experiencing anxiety. Anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HRS-A) before and after the structured implementation of the combined Mindfulness Breathing and Guided Imagery intervention. The evaluation showed a decrease in anxiety scores following the intervention; prior to the intervention, patients experienced moderate anxiety, which decreased to mild anxiety afterward. Patients also demonstrated more adaptive physiological and psychological responses, such as feeling calmer, improved focus, and better coping abilities. The combination of Mindfulness Breathing and Guided Imagery was proven to be effective in reducing anxiety in post–Sectio Caesarea mothers and may be used as an alternative nonpharmacological therapy in maternity nursing care to enhance postpartum psychological well-being.